HEADLINES, MEDIA VOCABULARY,BINGING (Ustozlar uchun, 2026)
This article examines the role of headlines, media vocabulary, and binge consumption of content in learning English as a foreign language. It highlights how exposure to authentic media sources such as news articles, social platforms, and streaming services can enhance vocabulary acquisition and comprehension skills. Special attention is given to the influence of headlines in shaping understanding and attracting learners’ attention. The concept of “bingeing,” or consuming large amounts of media content in a short time, is also analyzed as a modern learning strategy. The study concludes that integrating media-based learning techniques can significantly improve learners’ language proficiency and engagement.